Agroforestry potential in CDK IX's assisted areas of the Central Java Environment and Forestry Agency. Issue 1 (January 2021) - Prabawani, B; Warsono, H; Dewi, R S; Hapsari, N R
Abstract: Agroforestry is a form of sustainable farming that human needs, especially food, are met without jeopardizing future needs. Agroforestry is an urgent need, especially in highland areas in Central Java, which choose monoculture agriculture with high economic benefits but can damage the environment and endanger the ecosystem. Since 2017, the Government through the Regional Forestry Service Branch Office IX (CDK Wilayah IX), has guided farming communities in Magelang and Temanggung. However, the agroforestry output cannot be measured economically since the plant's age was only three years old. Using in-depth interviews and field observations, this study found that the CDK IX farming community has implemented agrosilvopastoral farming that there are arrangements for cropping and spacing patterns and agricultural support livestock. In addition, there is a pattern of alternate spatial rows that the planting rows were arranged. The potential for agroforestry success in this region was identified due to the support of government development through field extension workers, local leadership, and local wisdom. However, low community participation, low education and knowledge, and seeds acceptance from donors were not in the planting period.